Discursive decisions: Signposts to guide the use of critical discourse analysis in social work. (January 2022) - Willey-Sthapit, Claire; Jen, Sarah; Storer, Heather L; Benson, Odessa Gonzalez
Critical discourse analysis (CDA) examines the relationship between language and power in society. By linking micro, mezzo, and macro environments, examining the impact of language on marginalized communities, and providing a lens for critical reflection, CDA aligns with the frameworks and values of social work as a profession. Yet this method has been underutilized in social work research. This paper provides an orientation for social work scholars seeking to use CDA through discussion of four key "signposts" or decision-making points: 1) theoretical framing and rationale, 2) sampling and data generation, 3) data analysis, and 4) dissemination of findings. Drawing on examples from the authors' experiences with CDA studies addressing diverse research topics and methodological decisions, this paper offers a wide range of research design strategies for conducting similar projects. Examples are varied in terms of theoretical framing, research questions, data sources, analytic strategies, and audience. They include analyses of neoliberal discourse in refugee policy, discourses of culture in international development research documents, constructions of bisexuality among older women, and representations of intimate partner violence in young adult novels and tweets. Along the way, attention is given to communicating about CDA for social work audiences, particularly those less familiar with the epistemological foundations of CDA and its implications for practice.